Financial reforms and income inequality - Agnello, Luca (2012)
Using a panel of 62 countries for 1973-2005, we assess the impact of financial reforms on income inequality. We find that removal of policies towards directed credit and excessively high reserve requirements, and improvements in the securities market reduce inequality.